Diagnostic accuracy and prognostic significance of Glypican-3 in hepatocellular carcinoma: A systematic review and meta-analysis - Jiang, Donglei; Zhang, Yingshi; Wang, Yinuo; Xu, Fu; Liang, Jun; Wang, Weining (Frontiers in Oncology, 2022)
Purpose: Glypican-3 (GPC-3) expression is abnormal in the occurrence and development of Hepatocellular carcinoma (HCC).To explore whether GPC-3 has diagnosis accuracy and prognosis significance of HCC, we did a systematic review and meta-analysis. Method: PubMed, Embase, the Cochrane Library and China National Knowledge Infrastructure were searched with keywords of GPC-3, HCC and their MeSH terms from inception to July, 2022. We applied the hierarchical summary receiver operating characteristic model and evaluated the diagnostic value of GPC-3 alone and combination, and correlation between high and low GPC-3 expression on clinicopathological features and survival data in prognosis. Results: Forty-one original publications with 6305 participants were included, with 25 of them providing data for diagnosis value and 18 records were eligible for providing prognosis value of GPC-3. GPC-3 alone got good diagnosis value in HCC patients when compared with healthy control, moderate diagnosis value when compared with cirrhotics patients. Besides, combination of GPC-3+AFP and GPC-3+GP73 got great diagnosis value in HCC versus cirrhosis groups, the combination of GPC-3 can also improve the diagnostic accuracy of biomarkers. Moreover, we discovered that over expression of GPC-3 was more likely found in HBV infection, late tumor stage, microvascular invasion groups; and causes shorter overall survival and disease free survival, which means poor prognosis. Conclusion: GCP-3 could be used as a useful biomarker in HCC diagnosis and prognosis, especially in evaluated diagnostic value of combination with AFP or GP73, and forecast worse survival data of over-expression GPC-3.